Implikasi Keberangkatan Suami Merantau terhadap Pemenuhan Hak Istri: Analisis Perspektif Hukum Keluarga Islam - Ildayani; Robiatus Siddigiyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Marriage is a sacred bond aimed at establishing a harmonious, loving, and compassionate family, where the fulfillment of the rights and obligations between husband and wife is fundamental. This study examines the negative impact on wives who leave their homes from the perspective of Islamic Family Law, particularly regarding the dilemma between economic and biological needs. Using qualitative field methods with an empirical legal approach, this study projects in detail the negative impact of neglecting spiritual sustenance, which by nature cannot be set aside by a wife. The results of the study indicate a paradigm shift between the psychology of needs and desires, where the husband's physical absence often triggers negative impacts that threaten the integrity of the household. Legally, Islamic Family Law emphasizes that the husband's responsibilities after being transferred from his wife's guardianship include complete physical and spiritual protection. Consequently, a husband must carefully consider the sociological and biological impacts before deciding to leave his wife's home to avoid injustice to his wife's rights.